Multiculturalism and its discontents in SFR Yugoslavia and Bosnia: a critique of the multiculturalist rights model - Pupavac, Vanessa (Manchester University Press, 2005)
In this chapter I seek to contribute to debates over multiculturalism and highlight problems with ethnic rights strategies. I hope to facilitate understanding of the failures to overcome ethnic divisions in Bosnia, as well as to suggest how critiques of multiculturalism could be enriched by analysing the failures of ethnic rights policies in SFR Yugoslavia and Bosnia. I further wish to highlight the implications of the multiculturalist rights model for civil rights and freedoms. The imperative to secure peace in Bosnia has led to the international community overriding certain civil and political freedoms. These developments tend to be overlooked as exigencies of the immediate situation. Little unexplored is how multiculturalism involves very different expectations of the relationship between the State and the individual citizen in which rights come to be re-conceptualised as external rights of intervention and regulation. In this regard, the so-called third generation of rights is representative of the conformist, disciplinary side of the rights tradition as opposed to its emancipatory aspects.